Web-Based Bandwidth Configuration Automation Using Scheduling Algorithm - Dwipa Handayani; Andy Achmad Hendharsetiawan; Muhammad Ismam Maulana (LPPM Universitas Islam 45 Bekasi, 2025)
PT Mora Telematics Indonesia continues to be committed to providing the best service to satisfy customers, both in terms of the quality of the products offered and the responsiveness in handling requests. However, the process of requesting bandwidth on demand, especially in activating requests that still use conventional configurations, causes inefficiencies and the potential for human error. This can reduce customer satisfaction and hinder the speed of response to bandwidth upgrade requests. As an alternative, a solution is designed in the form of a bandwidth configuration automation system based on the priority scheduling algorithm with the aim of increasing efficiency and accuracy in managing bandwidth requests on demand. This application was developed using a waterfall development model and based on a unified modeling language with a website platform to ensure ease of use. Application functionality testing shows satisfactory performance in each process, both at the billing and NOC levels, and the priority scheduling algorithm is proven to be able to read the end-date on the bandwidth on demand data correctly